Serving the living and the dead: An integrated approach to Copper Age ceramic production and cultural dynamics in Campania, Southern Italy - Maria De Falco; Kamal Badreshany; Paola Aurino; Pierfrancesco Talamo; Robin Skeates (PLoS ONE, 2026)
This study explores the contribution of large scale integrated pottery analysis to the definition of broader cultural processes and, more specifically, highlights for the first time changes in the role and demand for ceramic objects during the Copper Age in Southern Italy. To identify such trends and drivers of change this study applies a holistic approach to ceramic production integrating typological analysis typical of the Italian tradition with a broader, theoretically informed, technological approach involving macroscopic observations and archaeometric analyses. The study area is Campania, in Southern Italy, where four multi-phase sites were selected spanning through the whole Copper Age (roughly 3800−2100 BC). This study represents the first large scale archaeometric programme on Copper Age contexts from southern Italy and allows us to detect and relatively dating technological innovations (such as the use of moulds and advances in the control of firing) as well as strong manufacturing traditions never previously fully characterised for Copper Age Southern Italy. The combination of typological and technological analyses of different ceramic assemblages highlighted the emergence in the Early/Middle Copper Age of a selected branch of production for complex funerary vessels deposed in collective graves linked to serving and consuming liquids. Towards the end of the 3rd millennium BC, important socio-economic and cultural dynamics led to a radical change in funerary practices in Central and Southern Italy and in the practical and symbolic role of ceramics in these contexts. Ceramic manufacture became more varied with no evidence of a dedicated funerary production, in fact, only few ceramic vessels, also common in domestic contexts, were generally deposed in single flat graves. This typological, productive and also symbolic disruption led to theorise a shift from a ‘ritual’ to a ‘functional’ demand for ceramic production, embedded in the cultural processes ongoing in this period. This integration of multiple lines of evidence (context, typology and technology) highlights how research on ceramics can contribute to the definition and understanding of larger phenomena at a regional and wider scale such as demands of production as well as symbolic, and economic drivers of change.